2009
DOI: 10.1016/j.labeco.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Counterfactual distributions with sample selection adjustments: Econometric theory and an application to the Netherlands

Abstract: Several recent papers use the quantile regression decomposition method of Machado and Mata (2005) to analyze the gender gap in log wages across the distribution. Since employment rates often differ substantially by gender, sample selection is potentially a serious issue for such studies. To address this issue, we extend the Machado-Mata technique to account for selection. In addition, we prove that this procedure yields consistent and asymptotically normal estimates of the quantiles of the counterfactual distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
161
3
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 25 publications
10
161
3
6
Order By: Relevance
“…The possibility of a relationship between the probability of women working and their having characteristics associated with higher wages (such as higher education found in De la Rica et al, (2008)) has been long recognised in the literature (Heckman 1979;Buchinsky 1998;Melly, 2006;Blundell et al, 2007;Albrecht et al, 2009). Olivetti and Petrongolo (2008) recently explore the non random presentation of women into employment and gender wage gaps (measured at the median of the distribution) for the US and a range of European countries (including the UK).…”
Section: Using Pooled Data For 1995-2001 From the European Community mentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility of a relationship between the probability of women working and their having characteristics associated with higher wages (such as higher education found in De la Rica et al, (2008)) has been long recognised in the literature (Heckman 1979;Buchinsky 1998;Melly, 2006;Blundell et al, 2007;Albrecht et al, 2009). Olivetti and Petrongolo (2008) recently explore the non random presentation of women into employment and gender wage gaps (measured at the median of the distribution) for the US and a range of European countries (including the UK).…”
Section: Using Pooled Data For 1995-2001 From the European Community mentioning
confidence: 99%
“…The Machado-Mata (MM) decomposition across the wage distribution methodology is further developed to account for sample selection by Albrecht et al, (2009) who decompose the gender gap among full-time workers in the Netherlands.…”
Section: Using Pooled Data For 1995-2001 From the European Community mentioning
confidence: 99%
See 1 more Smart Citation
“…The second term measures the "unexplained" portion of the homeownership gap. Albrecht et al (2006) have shown that the decomposition is consistent and asymptotically normal.…”
Section: Machado-mata Decompositionmentioning
confidence: 83%
“…This study implements a new decomposition technique that identifies the unexplained portion of the gap not only at the mean, but at every percentile of the distribution of the dependent variable. This method was first proposed by Machado and Mata (2005), extended by Albrecht et al (2006), and has been used in several applications in labor economics. Similar to the labor market application, differences in homeownership gaps at the mean reflect a combination of nonsignificant differences at the upper end and much larger gaps at the lowest end of the distribution of homeowners.…”
mentioning
confidence: 99%